Antibacterial and antibiofilm activity of silver nanoparticles stabilized with C-phycocyanin against drug-resistant Pseudomonas aeruginosa and Staphylococcus aureus - Chegini, Zahra; Shariati, Aref; Alikhani, Mohammad Yousef; Safaiee, Maliheh; Rajaeih, Shahin; Arabestani, Mohammadreza; Azizi, Mehdi (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Biofilms are bacterial communities that can protect them against external factors, including antibiotics. In this study, silver nanoparticles (AgNPs) were formed by modifying AgNPs with C-phycocyanin (Ag-Pc) to inhibit the growth of carbapenem-resistant Pseudomonas aeruginosa (CR P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) and destroy biofilm of these bacteria.The AgNPs were prepared with the green synthesis method, and Pc was used to stabilize the AgNPs. The Ag-Pc's antibacterial and antibiofilm effects were evaluated using the Microbroth dilution method and microtiter plate assay. The inhibitory effect of Ag-Pc on the expression of biofilm-related genes was evaluated by real-time PCR. Moreover, the MTT assay was used to assess the Ag-Pc toxicity.The Ag-Pc minimum inhibitory concentration (MIC) was 7.4 µg/ml for CR P. aeruginosa and MRSA. Pc did not show antibacterial effects against any of the strains. Ag-Pc suppressed biofilm formation and destroyed matured biofilm in both bacteria more efficiently than the AgNPs (P<0.05). The expression of all genes was not significantly reduced in the presence of synthesized nanoparticles. Finally, the MTT assay results did not show toxicity against a murine fibroblast cell line (L929) at MIC concentration.The present study showed the promising potential of Pc for improving the antibacterial and antibiofilm function of AgNPs and inhibiting drug-resistant bacteria. Therefore, Ag-Pc nanoparticles can be considered a promising therapeutic approach for the managing of the bacterial biofilm.